Effect of Breed and Finishing Diet on Growth Parameters and Carcass Quality Characteristics of Navarre Autochthonous Foals - Aurora Cittadini; María V. Sarriés; Rubén Domínguez; Gregorio Indurain; José M. Lorenzo (Animals, 2021)
This research was conducted to study the effect of breed, Jaca Navarra (JN) vs. Burguete (BU), and finishing diet, conventional concentrate—diet 1 vs. silage and organic feed diet 2—on growth parameters and carcass characteristics from forty-six foals. Parameters as live weight (LW), average daily gain (ADG), body condition score (BCS), and fat depots were monitoring. In addition, the carcass parameters assessed were: carcass weight (CW), conformation, degree of fatness, morphology, and pH. Moreover, hindquarters of the left-half carcasses were sectioned in the main commercial primal cuts of leg. Results showed a clear “breed effect” in favor of BU foals, recording the highest productive values and carcass traits compared with JN foals. On the other hand, finishing diet contributed to improving the productive and carcass features of JN foals. In particular, diet 1 showed to affect positively the features analyzed compared with diet 2. Nevertheless, the meat primal cuts resulted in being unaffected by the breed and diet effects (except for knuckle), obtaining similar values among the groups of animals.